Non-null Distribution of The Likelihood Ratio Statistic for Testing Multisample Compound Symmetry (2004)
ABSTRACT: The non-null distribution of the modiﬁed likelihood ratio test statistic Λ∗ for testing multisample compound symmetry of q multivariate Gaussian models is derived. The non-null moments of Λ∗ are obtained in terms of Lauricella's hypergeometric function. The non-null distribution is expressed in terms of H-function.